Influence of farm radio international radio programmes on farmers in Oyo State, Nigeria - Shodipe, Oluwafunmilayo Abimbola; Sanusi, Bernice O.; Talabi, Felix O.; Adelabu, Omowale T. (Corpus Intellectual, 2024)
The paper sought to investigate the influence of FRI radio programmes on farmers' knowledge, skills, and practices in Oyo state. The study was anchored on the Uses and Gratifications theory. The paper opted for a Mixed Methods research design, using Survey and Focus Group Discussion (FGD) to gather data from farmers. Findings indicated that exposure to FRI radio programmes is low among AFAN members who have not been mobilised by FRI. In contrast, exposure was high among FGD farmers who had previously been mobilised by FRI to listen to the radio programmes. Findings also showed that radio is effective in influencing the practices of farmers and helping them adopt new agricultural knowledge, skills and practices. It concludes that FRI radio programmes positively influence farmers and enhance their capacity. The study recommends that FRI and partners mobilise farmers from farmer's associations like AFAN for the radio programmes.